2014
DOI: 10.1007/s10995-014-1493-0
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Child Health Care Utilization by Medical Complexity

Abstract: Objectives Children with medical complexity (CMC) have multiple specialty need, technology dependence, and high health care utilization. The objective of this study is to profile types of pediatric health care utilization and costs by increasing levels of medical complexity. Methods Cross-sectional study of the 2007, 2008 and 2009 Full-Year Data Sets from the Medical Expenditure Panel Survey. Medical complexity was defined by a higher number of positive items from the five question Children with Special Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 30 publications
(46 reference statements)
4
60
0
Order By: Relevance
“…[1][2][3][4][5][6] In recent years, there has been a significant rise in innovative clinical programs targeting this population of children. 7 Health plans, children's hospitals, and other entities are enrolling high-cost children into care management programs to improve their health.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] In recent years, there has been a significant rise in innovative clinical programs targeting this population of children. 7 Health plans, children's hospitals, and other entities are enrolling high-cost children into care management programs to improve their health.…”
mentioning
confidence: 99%
“…85% of children in the TeleFamilies Project had multiple complex chronic conditions, and approximately half required life-sustaining technology assistance. Previous studies of health care service use in this population have shown a correlation between increasing positive responses on the CSHCN screener and the number of hospital visits (Cohen et al, 2012; Kuo et al, 2014). …”
Section: Discussionmentioning
confidence: 78%
“…There is evidence in wider literature on the care of children with CCNs that there are numerous and varied characteristics of a family that need to be understood to support family preparedness for discharge to home that goes well beyond clinical readiness to care. This includes issues relating to language, culture, race and ethnicity [24][25][26], family structures and support systems [27][28][29] and capacity for coping [30][31][32]. The fact that the majority of countries do not currently collect data on the experience of care from the perspective of the parents/guardians or siblings of children assisted with LTV, suggests a persistent paternalistic health service with a limited appetite for identifying and addressing the real needs of the child and family.…”
Section: Discussionmentioning
confidence: 99%